Hubungan Brand Image dengan Customer Loyalty pada Pengguna Telkomsel Kalangan Mahasiswa Psikologi - Dji Saputra Togatorop, Ricky; Rahma Nio, Suci (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The main purpose of this research is to describes the relationship brand image with customer loyalty in Padang University . The type of this research is correlational quantitative. The population were in Bukittinggi with 60 who have matched the characteristics of this research that gained by purposive sampling. Data was collected use brand image scale with reliability value is 0.888 and customer loyalty scale with reliability value is 0.864. Data were processed using statistical technique of corelational product moment by Karl Pearson. The result from these finding in research are r=0.744 and p=0.000 (p<0.01) which mean it showed there was very significant positive relationship between brand image with customer loyalty